The effect of protein and acid source on growth and carcass characteristics in growing Boer goats - Nelson, Joel A.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
With a growing population of goats in the United States; there is an increasing demand on knowledge of how the goat grows and functions because of limited research data. Therefore; the objective of this study is to evaluate the impact of varying protein source and acid source on feedlot growth and carcass traits on growing boar goats. Due to recent findings, and an estimated elevated level of bypass protein requirement, it was hypothesized that the diet with higher bypass protein would provide better growth than diets with lower bypass protein. To test this hypothesis, seventy-five Boer goats (Starting BW 52lbs) were allocated to 5 treatments in a completely random design held at the Kansas State University Sheep and Meat Goat Center. Goats were split by average BW into 25 pens (5 pens/treatment; 3 goats/pen) for a 42 d performance study. Diets were isonitrogenous and isocaloric and were split by varying protein and acid source. Treatment 1) Soybean Meal (SBM) and Ammonium Chloride (AmCL); 2) Dried distillers’ grains with solubles (DDGS) and AmCl; 3) SoyPlus and AmCL; 4) SBM and SoyChlor; 5) SoyPlus and SoyChlor. Goats were placed on a self-feeder with all access to water. Body weights were taken every 7 days along with feeder weights and feed added. After the 42 d period, BW, ADG, ADFI, G:F were measured and compared. There were no significant differences in the BW (P>0.05), ADG (P>0.05), ADFI (P>0.05), and G:F (P>0.05) detected within the study. There were significant differences in the economic cost of treatments and goat gains. When comparing the cost per Kg of gain DDGS cost less than SBM (P<0.05) and less than SoyPlus (P<0.05). These results show that feeding DDGS compared to other protein sources can be very valuable to increase profit margins.
Keywords: Fall 2018